Decay of infectious SARS-CoV-2 and surrogates in aquatic environments. (1st August 2021) - Sala-Comorera, Laura; Reynolds, Liam J.; Martin, Niamh A.; O'Sullivan, John J.; Meijer, Wim G.; Fletcher, Nicola F.
Highlights: T90 of infectious SARS-CoV-2 at 4°C was 3.8 and 2.2 days in river and seawater T90 of infectious SARS-CoV-2 at 20°C was 2.3 and 1.1 days in river and seawater SARS-CoV-2 RNA is more stable than the infectious particle in river and seawater Infectious MS2 persisted longer than infectious SARS-CoV-2 in aquatic environments The decay rate of MS2 and PMMoV RNA differed from the decay rate of SARS-CoV-2 RNA Abstract: The introduction of SARS-CoV-2 containing human stool and sewage into water bodies may raise public health concerns. However, assessment of public health risks by faecally contaminated water is limited by a lack of knowledge regarding the persistence of infectious SARS-CoV-2 in water. In the present study the decay rates of viable infectious SARS-CoV-2 and SARS-CoV-2 RNA were determined in river and seawater at 4 and 20°C. These decay rates were compared to S. typhimurium bacteriophage MS2 and pepper mild mottle virus (PMMoV). Persistence of viable SARS-CoV-2 was temperature dependent, remaining infectious for significantly longer periods of time in both freshwater and seawater at 4°C than at 20°C. T90 for infectious SARS-CoV-2 in river water was 2.3 days and 3.8 days at 20°C and 4°C, respectively. The T90 values were 1.1 days and 2.2 days in seawater at 20°C and 4°C, respectively. In contrast to the rapid inactivation of infectious SARS-CoV-2 in river and sea water, viral RNA was relatively stable. The RNA decay rates were increased in non-sterilised river and seawater, presumably due to the presence of microbiota. The decay rates of infectious MS2, MS2 RNA and PMMoV RNA differed significantly from the decay rate of SARS-CoV-2 RNA, suggesting that their use as surrogate markers for the persistence of SARS-CoV-2 in the environment is limited. Graphical Abstract: Image, graphical abstract